PROFIL KEMAMPUAN BERPIKIR KREATIF PERSERTA DIDIK KELAS VI SDN GANDEKAN NO. 230 SURAKARTA DITINJAU DARI PRESTASI AKADEMIK - Jumanto, Jumanto; Adi, Yogi Kuncoro (FKIP, PGSD, Universitas Slamet Riyadi, 2023)
This study aims to determine the profile of the creative thinking ability of class VI students of SD Negeri Gandekan No. 230 Surakarta who have below-average and above-average academic achievements. This research includes quantitative research. Data are collected by means of observation, interviews, and tests. The study sample was 34 learners. To determine the profile of students' creative thinking ability, this study used discriptive analysis. Meanwhile, to find out the difference in creative thinking ability between students who have academic achievements above and below average, using an independent T-Test analysis. The results showed that the creative thinking of students in kategori was good (71.38). With the following details: fluency indicators in the good category (78), flexibility in the good category (75.5), originality in the good category (73) and elaboration in the sufficient category (61). The T-Test value is sig.0.52>0.05 which means that the ability to think creatively between outstanding learners ak ademik up and down is considered to have no significant difference.